2020
DOI: 10.2147/rrtm.s244912
|View full text |Cite
|
Sign up to set email alerts
|

<p>Basic Coagulation Profiles and Platelet Count Among <em>Schistosoma mansoni</em>-Infected Adults Attending Sanja Primary Hospital, Northwest Ethiopia</p>

Abstract: Purpose: To assess basic coagulation profiles and platelet count among Schistosoma mansoni-infected and non-infected adults. Patients and Methods: A comparative cross-sectional study was conducted from February to April 2019 at Sanja Primary Hospital, northwest Ethiopia. A total of 200 adults (100 cases and 100 controls) were enrolled using convenient sampling technique. Both wet mount and Kato-Katz techniques were performed using a stool sample. The venous blood sample was collected to perform platelet count,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 31 publications
4
12
1
Order By: Relevance
“…The Kruskal–Wallis H-test showed that there was a significant difference in PT, APTT, and INR values between the intensity of infection and apparently healthy controls. This finding was in line with the report from Sanja Primary Hospital, Northwest Ethiopia [ 30 ]. The difference in platelet parameters between healthy controls and the intensity of S. mansoni infection in adults was not statistically significant.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The Kruskal–Wallis H-test showed that there was a significant difference in PT, APTT, and INR values between the intensity of infection and apparently healthy controls. This finding was in line with the report from Sanja Primary Hospital, Northwest Ethiopia [ 30 ]. The difference in platelet parameters between healthy controls and the intensity of S. mansoni infection in adults was not statistically significant.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, in the present study, the platelet parameters (MPV and PDW) were also significantly different between S. mansoni -infected adults and healthy controls ( P value ≤ 0.001). This finding was similar to studies done in Northwest Ethiopia [ 30 ], in Brazil [ 16 ], and Western Burkina Faso [ 31 ]. The MPV was significantly decreased among S. mansoni -infected adults compared to healthy controls.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The thrombocytopenia recorded in S . mansoni infected-untreated mice in this study is in conjunction with several authors who demonstrated that a low blood platelet count is associated with Schistosoma infection in mice [ 58 60 ] or humans [ 61 , 62 ]. Stanley et al [ 60 ] reported that thrombocytopenia occurs in S .…”
Section: Discussionsupporting
confidence: 86%
“…In this instance, the coagulopathy and thrombocytopenia could represent hematologic manifestations of S. mansoni , and the coagulation profile and platelet count should be obtained to examine both the treatment response and complications. 37 …”
Section: Discussionmentioning
confidence: 99%